2022
DOI: 10.1177/00076503221097298
|View full text |Cite
|
Sign up to set email alerts
|

Building on Its Past: The Future of Business and Society Scholarship

Abstract: This Special Issue commemorates the 60th anniversary of Business & Society with nine rigorous literature reviews that address important societal problems and provide opportunities for theory development in the business and society field; in this introduction we present an overview of the Special Issue. With the theme “Building on Its Past,” the nine articles address a host of contemporary issues, including climate change, wicked problems, business and human rights, human health, certifications standards, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In conclusion, as we noted in our introduction to the 60th-anniversary special issue (Brown et al, 2022), business and society issues are gaining an increasing attention from the mainstream management scholars as well as the stakeholders of business research. The effects of the pandemic and climate change have now touched all of us in one way or another and have added more salience to our scholarship.…”
Section: From Theorizing Through Context To Affectmentioning
confidence: 74%
“…In conclusion, as we noted in our introduction to the 60th-anniversary special issue (Brown et al, 2022), business and society issues are gaining an increasing attention from the mainstream management scholars as well as the stakeholders of business research. The effects of the pandemic and climate change have now touched all of us in one way or another and have added more salience to our scholarship.…”
Section: From Theorizing Through Context To Affectmentioning
confidence: 74%
“…It is critical in business learning to employ an open systems approach, which includes employing methodologies to address complex causes, employing theories and perspectives that include external and internal organizational elements, and reflecting on the temporal and spatial dynamics of complex systems. As according Brown et al [6], future business education should include a more systemic and integrative perspective to study the complex interactions that link business actors, issues, and society, as well as a more open approach that supports contextual aspects as well as multi-level and multi-disciplinary approaches to address society's great challenges.…”
Section: Business Education Learning Design Post Pandemicmentioning
confidence: 99%
“…Such a mandate calls for empirical and theoretical attention to how organizations influence and shape the trajectories of social systems and expands traditional ways of studying how organizations address or are affected by GC (Mair & Seelos, 2021). Illustrations for a traditional perspective are Brown et al (2022), who identified organizational survival as the key dependent variable in GC research, or Voegtlin et al (2022), who identified responsible innovation as an approach by which businesses help solve GC. A third mandate perspective expands a focus on solving GC towards imagining and assessing possibilities and roles for organizations to generate fewer 'grand' problems in the first place (Ackoff, 1981).…”
Section: Broadening Our Theoretical Scopementioning
confidence: 99%
“…Illustrations for a traditional perspective are Brown et al. (2022), who identified organizational survival as the key dependent variable in GC research, or Voegtlin et al. (2022), who identified responsible innovation as an approach by which businesses help solve GC.…”
Section: Towards Principles For Management Research On Challenges Of ...mentioning
confidence: 99%